Feedback for Effective Learning: Stumbling Blocks/ Learning Barriers in Communication between Learning and Teaching - Sharma, Dr. Mukti Ashu Pragya; Sharma, Dr. Deepti (American Journal of Humanities and Social Sciences, 2017)
Feedback is an integral part of communication. It renders an opportunity to evaluate the success of communication. In case of classroom learning, feedback plays an important role as it makes the learning process smooth. It is effective for students and teachers in analyzing the performance and designing the teaching methodology. The feedback given by teachers to the students about their work and performance is equally important to the feedback given by students about their understanding regarding the topic taught by the teachers. The importance of feedback is widely known and it covers students’ motivation, their willingness to prove themselves and their confidence in the learning process. It is also required to identify and evaluate the barriers in communication between the teachers and the students. To accomplish this purpose a well-structured survey was conducted covering approximately sixty five students. As per the result of the surveys students showed lack of interest in open interaction in the class. Non-native English speaking students felt language as a barrier. Students felt difficulties in understanding the content. Students faced problems to understand the instructions given by the teacher. The stumbling blocks that affect the feedback process should be effectively removed to provide solution to help both students and teachers to communicate well. Two way feedback is important in continuous improvement in teaching and learning. Teacher and students’ feedback to each other not only enhances the learning of students but it also improves the teaching methodology based on the feedback provided.